Nitric Oxide as a Potential Adjuvant Therapeutic for Neuroblastoma: Effects of NO on Murine N2a Cells - Gordon, Jenna L. (Vet Sci, 2020)
Neuroblastoma, the most common extracranial solid tumor in children, accounts for 15% of all pediatric cancer deaths. Pharmaceutical applications of S-Nitrosylation, which, under normal conditions is involved with a host of epigenetic and embryological development pathways, have exhibited great potential for use as adjuvant therapeutics in the clinical management of cancer. Herein, an evaluation of the impact of nitric oxide (NO) as a potent anticancer agent on murine neuroblastoma cells is presented. Excitingly cell viability, colony formation, and non-carcinogenic cell analysis illustrate the significance and practicality of NO as a cytotoxic anticancer therapeutic. Resazurin, WST-8 (2-(2-methoxy-4-nitrophenyl)-3-(4-nitrophenyl)-5-(2,4-disulfophenyl)-2H-tetrazolium, monosodium salt), and MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-diphyltetrazolium bromide) assays consistently displayed a moderate, ~20–25% reduction in cell viability after exposure to 1 mM S-Nitrosoglutathione (GSNO). A colony formation assay demonstrated that treated cells no longer exhibited colony formation capacity. Identically GSNO-treated Adult Human Dermal Fibroblasts (HDFa) exhibited no decrease in viability, indicating potential discrimination between neoplastic and normal cells. Collectively, our findings indicate a potential application for NO as an adjuvant therapeutic in the clinical management of neuroblastoma.